Typifications in the genus Dichanthium (Andropogoneae: Poaceae) - Shaikh, Tarbej; Ghalme, Raghunath; Potdar, Girish (Phytotaxa, 2022)
Dichanthium aristatum (Poir.) C.E. Hubb, D. foulkesii (Hook.f.) S.K. Jain & Deshp., D. mccannii Blatt., D. panchganiense Blatt. & McCann and D. paranjpyeanum (Bhide) Clayton are lectotypified, the selection of lectotype is discussed.